Magnetic nanoparticle catalyst for hydrogenation of furfural to biofuel / Ahmed Halilu - Ahmed , Halilu (2016)
The growing global energy demands as a result of population increase, the excessive dependency on depleting fossil oil, and the health-environmental issues posed by fossil oil have prompted the need for clean energy alternative via renewable energy options. Consequently, this study was undertaken to solve these energy issues via heterogeneous catalysis. A simple repeating unit of Fe(MFe)O4-SiO2 (M = Ni, Ru) heterogeneous catalyst was design, built and optimized on Gaussian computational platform using the mechanics method and universal force field (UFF) functional. Data on vibrational spectroscopy of metal to point charge linkages of simple repeating unit of the catalyst was acquired. This was preceded with experimental one-pot synthesis at ambient condition into a novel template free mesoporous magnetic Fe(MFe)O4-SiO2 nanoparticle catalyst. The experimental vibrational modes were corroborated with the computational vibration modes to mark the outstanding capacities of the catalyst in hydrogenation of biomass derived oxygenates to biofuel. The catalysts physicochemical properties were confirmed using Raman Spectroscopy, X-ray Diffraction (XRD), Atomic Force Microscopy (AFM), High Resolution Transmission Electron Microscopy (HRTEM), Field Emission Scanning Electron Microscopy (FESEM), Vibrating Sample Magnetometer Analysis (VSM), and X-ray Photoelectron Spectroscopy (XPS). As a parameter to confirm the catalyst inverse spinel structure, the crystal field stabilization energy (CFSE) for Ni, Ru and Fe n+ phases in the catalyst were quantitatively evaluated as; CFSE-Fe 2+ ~ -4.03578 ×10−10 eV and CFSE-Fe 3+ 0 eV, CFSE-Ni 2+ ~ -7.4388 ×10−11 eV and CFSE-Ru 3+ ~ -10.7618 ×10−11 eV. The active Ni 2+ and Ru 3+ component incorporation at the octahedral site was confirmed with the octahedral site preference energy (OSPE) values being; OSPE Ni 2+ ~ -5.2347 ×10−11 eV and OSPE for Ru 3+ ~ -7.4883 ×10−11 eV. In addition, super paramagnetic physical properties of the catalyst with low coercivity of 6.991 G for Fe(MFe)O4-SiO2 catalyst compared with 27.323 G for Fe3O4-SiO2 core shell geometry supports the OSPE. These are intrinsic properties that were confirmed to reveal the extrinsic properties such as BET nitrogen adsorption analysis mesoporosity of the catalyst as corroborated with AFM revealing approximately < 20 nm pore sizes and 14.32 nm particle sizes from XRD and HTREM analysis. The catalyst showed redox property at 400-500 oC and makes it potentially effective for hydro-processing reactions. Correspondingly, > 92 % conversion of furfural to furfuryl alcohol at 90-250 oC and 5-20 bar was observed during hydrogenation reaction over Fe(MFe)O4-SiO2 catalyst. Also, 100% conversion of furfural to furfural alcohol, pentane and tetrahydrofuran; and vanillin to vanillyl alcohol, guaiacol, cyclohexane, cyclohexanol and cyclohexanone was observed at 250 oC and 90 bar over the catalyst. With the aid of time dependent density functional theory on B3LYP functional that revealed the highest occupied molecular orbital and the lowest unoccupied molecular orbital of furfural and vanillin, GC-MS and GC-FID, TPR analysis, a probable mechanism via a non-hydrogen spillover route was proposed for the formation of the aforementioned biofuel molecules. The catalyst recorded six cycles of reusability and ~100 % recoverability.